Antibody Tests: They are More Important than We Thought - Luis Guimaraes (Queen's University Belfast, Queen's Management School, 2020)
Antibody testing is a non-pharmaceutical intervention - not recognised so far in the literature - to prevent COVID-19 contagion. I show this in a simple economic model of an epidemic in which agents choose social activity under health state uncertainty. In the model, susceptible agents are more socially active when they think they might be immune. And this increased activity escalates infections, deaths, and welfare losses. Antibody testing, however, prevents this escalation by revealing that susceptible agents are not immune. Through this mechanism, in exercises calibrated to the UK, I find that antibody testing can save about 8% of COVID-19 related deaths within 12 months
Keywords: D62; E17; I12; I18; 330